Cascadic Multigrid in a Spectral‐Element Context. Issue 1 (25th October 2016) - Huismann, Immo; Stiller, Jörg; Fröhlich, Jochen
Abstract: Current research in computational fluid dynamics focuses on high‐order methods, which offer a significant reduction of the computational effort for a given error bound. In low‐order methods optimal complexity solvers for elliptic equations, e.g. the Helmholtz equation, are readily available, but for high‐order methods these are still an area of research. This work evaluates the effectiveness of the Cascadic Multigrid Method in the context of spectral elements, comparing it to a standard Krylov subspace solver. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)